Fallen feathers in Thunder Bay: How Canada's newspapers implicate Indigenous youth - Gabriele, Chelsea Brianne (2018)
This study asks how the media perpetuates the cycle of racism, colonialism and stereotyping of Indigenous youth in Thunder Bay, and how Indigenous news sources participate in giving voice to Indigenous peoples. The research methodology is a discourse analysis examining both mainstream and Indigenous newspaper articles on the subject of the First Nations youth deaths in Thunder Bay. The methodology is also influenced by critical and decolonizing theories. Findings show that Indigenous newspaper articles are overall more inclusive of Indigenous voice, therefore providing an Indigenous perspective on the issue of First Nations youth dying in Thunder Bay and leaving out racist portrayals. On the other hand, non-Indigenous newspaper articles include less Indigenous voice and use the opinion of individuals in powerful positions. They also tend to portray Indigenous people in a negative light when compared to Indigenous newspapers. Outcomes from this research include implications for social workers such as: developing an understanding of how the media perpetuates racism, colonialism and stereotyping against Indigenous youth, advocating for and empowering Indigenous youth so they can come together and fight for change in First Nations education, and improving education within schools of social work regarding advocacy in the media. Thesis Master of Social Work (MSW)